Biochemical Composition And Antioxidant Capacity Of Marine Microalgae Chlorella salina Butcher AND Isochrysis maritima Billard and Gayral Isolated From Penang Coastal Waters - Siti Syazwina, Shahar (2014)
Chlorella salina and Isochrysis maritima were successfully isolated, purified and cultured in Conway medium. Morphology and ultra-structures of strains were observed using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Chlorella salina dan Isochrysis maritima berjaya dipencil, ditulenkan dan dikultur di dalam medium Conway. Morfologi dan struktur-ultra strain telah dipantau menggunakan mikroskop elektron pengimbas (SEM) dan mikroskop elektron transmisi (TEM).